Phenotypic Identification of a Novel Autophagy Inhibitor Chemotype Targeting Lipid Kinase VPS34. (12th June 2017) - Robke, Lucas; Laraia, Luca; Carnero Corrales, Marjorie A.; Konstantinidis, Georgios; Muroi, Makoto; Richters, André; Winzker, Michael; Engbring, Tobias; Tomassi, Stefano; Watanabe, Nobumoto; Osada, Hiroyuki; Rauh, Daniel; et al.
Abstract: Autophagy is a critical regulator of cellular homeostasis and metabolism. Interference with this process is considered a new approach for the treatment of disease, in particular cancer and neurological disorders. Therefore, novel small‐molecule autophagy modulators are in high demand. We describe the discovery of autophinib, a potent autophagy inhibitor with a novel chemotype. Autophinib was identified by means of a phenotypic assay monitoring the formation of autophagy‐induced puncta, indicating accumulation of the lipidated cytosolic protein LC3 on the autophagosomal membrane. Target identification and validation revealed that autophinib inhibits autophagy induced by starvation or rapamycin by targeting the lipid kinase VPS34.